Hierarchically ordered ABA triblock copolymer with large difference in glass transition temperatures of the two blocks. Issue 12 (3rd April 2014) - Li, Chang‐Feng; Zhang, Qi‐Kai; Tian, Hai‐Jian; Chai, Chun‐Peng; Gao, Long‐Cheng; Shen, Zhihao; Fan, Xing‐He; Luo, Yun‐Jun
ABSTRACT Rod‐coil‐rod triblock copolymers, poly[4′‐(methoxy)‐2‐vinylbiphenyl‐4‐methyl ether] ‐blockpolydimethylsiloxane‐block‐poly[4′‐(methoxy)‐2‐vinylbiphenyl‐4‐methyl ether] (PMVBP‐b‐PDMS‐b‐PMVBP), were synthesized by nitroxide‐mediated radical polymerization, and their hierarchically ordered structures were studied. A difunctional TEMPO macroinitiator was first synthesized by the hydrosilylation reaction between hydride‐endcapped PDMS and allylic alkoxyamine. The polymerization of the monomer MVBP was triggered by the macroinitiator, resulting in a series of triblock copolymers. The molecular weights and polydispersity indexes were determined by gel permeation chromatography. Differential scanning calorimetry results demonstrate that the triblock copolymers exhibit two glass transition temperatures (−120 °C and 160 °C) that are markedly different. As revealed by small‐angle X‐ray scattering and transmission electron microscopy experiments, the triblock copolymers self‐assemble into hierarchical structures with the liquid crystalline phase of PMVBP in the lamellar structures. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1737–1744